A Critique of the Uganda District League Table using a Normative Health System Performance Assessment Framework - Tashobya, Christine Kirunga; Ssengooba, Freddie; Nabyonga-Orem, Juliet; Bataringaya, Juliet; Marchal, Bruno; Criel, Bart (BMC health services research, 2018)
In 2003 the Uganda Ministry of Health (MoH) introduced the District League Table (DLT) to track district performance. This review of the DLT is intended to add to the evidence base on Health Systems Performance Assessment (HSPA) globally, with emphasis on Low and Middle Income Countries (LMICs), and provide recommendations for adjustments to the current Ugandan reality.A normative HSPA framework was used to inform the development of a Key Informant Interview (KII) tool. Thirty Key Informants were interviewed, purposively selected from the Ugandan health system on the basis of having developed or used the DLT. KII data and information from published and grey literature on the Uganda health system was analyzed using deductive analysis.
Keywords: Decentralization; Health system; Decision-making; Accountability; Performance assessment